EFL student teachers’ beliefs about contemporary language teaching approaches - Lőrincz György; Леврінц Юрій; Levrints Marianna; Lőrincz Marianna; Леврінц Маріанна (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2026)
Abstract. Beliefs held by aspiring EFL teachers are foundational to their pedagogical practices, affecting their conceptualization, evaluation, and implementation of contemporary language teaching approaches. In the context of the reform movement “New Ukrainian School,” disclosing the nature of these beliefs is critical to implementing the stipulated innovations into classroom practices. Therefore, this study explored prospective language teachers’ beliefs regarding contemporary and traditional language teaching. A survey was conducted among 64 final-year undergraduate students enrolled in an English Language and Literature education program. The questionnaire assessed their beliefs across domains of language instruction, such as goals, classroom procedures, language use, and teacher/learner roles. Quantitative data analysis revealed a strong preference for principles underlying contemporary language teaching, particularly those emphasizing fluency, target language use, and cooperative learning. However, the respondents also expressed moderate support for aspects of traditional language teaching, such as explicit grammar instruction, accuracy, repetition, and teachercenteredness. Such duality suggests students’ inclination for eclecticism and postmethod pedagogy, where pre-service teachers selectively apply principles from both instructional paradigms to suit specific contexts. The findings point to the complexity of beliefs development during initial teacher education, underscoring the need for targeted methodological intervention to raise students’ awareness of their tacit beliefs.

Резюме. Стаття присвячена дослідженню поглядів майбутніх учителів англійської мови як іноземної щодо традиційних і сучасних підходів до викладання іноземних мов. З урахуванням пріоритетів освітньої політики України, визначених реформою «Нова українська школа», яка орієнтується на формування іншомовної комунікативної компетентності, актуалізується необхідність вивчення рівня готовності студентів до впровадження інноваційних змін у професійній діяльності. У зв’язку з цим метою дослідження є з’ясування ставлення здобувачів вищої освіти до доцільності застосування сучасних лінгводидактичних підходів і методів, а також виявлення їхніх професійних уподобань. У дослідженні використано метод анкетування з подальшою статистичною обробкою даних. Вибірку становили шістдесят чотири здобувачі першого (бакалаврського) рівня вищої освіти, які завершили виробничу педагогічну практику на четвертому курсі. Результати аналізу засвідчили переважну підтримку сучасних лінгводидактичних принципів, таких як орієнтація на формування іншомовної комунікативної компетентності, використання англійської мови як основного засобу комунікації під час занять, а також організація роботи у групах і парах. Водночас респонденти частково визнають доцільність використання традиційних підходів — зокрема, через акцент на граматичній точності, експліцитне навчання граматики та провідну роль викладача. Отримані результати свідчать про прагнення студентів до еклектичного підходу у викладанні іноземних мов, що передбачає гнучке поєднання різних методик залежно від освітнього контексту та потреб здобувачів освіти.

A leendő angol mint idegen nyelv tanárok véleményei és attitűdjei alapvetően meghatározzák pedagógiai gyakorlatukat, ezáltal befolyásolva a kortárs nyelvoktatási megközelítések értelmezését, értékelését és használatát. Az „Új ukrán iskola” oktatási reform kontextusában e vélekedések természetének feltárása kulcsfontosságú az előírt innovációk tantermi gyakorlatba való bevezetéséhez. Ennek megfelelően a kutatás a leendő nyelvtanárok kortárs és hagyományos nyelvoktatással kapcsolatos nézeteit vizsgálta. A felmérést 64 végzős BA-hallgató körében végeztük el, akik angol nyelv és irodalom tanárképzésben vettek részt. A kérdőív a nyelvoktatás különböző területeire vonatkozó nézeteket mérte fel, mint például az oktatás céljai, a tanórai eljárások, a nyelvhasználat, valamint a tanár és a tanuló szerepkörei. A kvantitatív adatelemzés erős preferenciát mutatott a modern nyelvoktatás alapelvei iránt, különösen a folyékony nyelvhasználat, a célnyelv alkalmazása és az együttműködésen alapuló tanulás hangsúlyozása tekintetében. Ugyanakkor a válaszadók mérsékelt támogatást fejeztek ki a hagyományos nyelvoktatás egyes elemei iránt is, mint az explicit nyelvtanoktatás, a grammatikai pontosság, az ismétlés és a tanárközpontúság. Ez a kettősség a hallgatók eklektikus szemléletére és a posztmetódus pedagógia iránti nyitottságára utal, amelyben a tanárjelöltek mindkét oktatási paradigmából szelektíven alkalmaznak elveket az adott kontextushoz igazodva. Az eredmények rávilágítanak a tanárszakos hallgatók nézeteinek összetettségére a tanárképzés során, és hangsúlyozzák a célzott módszertani beavatkozások szükségességét a hallgatók rejtett attitűdjeinek tudatosítása érdekében.
Погляди майбутніх учителів іноземних мов на сучасні лінгводидактичні підходи
Az angol szakos tanár jelöltek nézetei a modern nyelvoktatási megközelítésekről
Teljes kiadvány: https://aab-philologica.kmf.uz.ua/aabp/issue/view/11/20
Keywords: English as a foreign language; learning; teacher beliefs; EFL student teachers